2018
DOI: 10.1177/1012690218789037
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and opportunity: A study of dual career, aspirations and elite sports in Danish SportsClasses

Abstract: In this article we analyze the patterns of retention in SportsClasses of promising young athletes in Denmark. Since 2005, SportsClasses have provided extra training for potential elite athletes in Grades 7–9 in designated Danish public schools. They were introduced after the Danish Ministry of Culture lowered the age of recruitment for athletes from 15 to 12 in response to increased competition in the world of elite sports. The SportsClasses attempt to balance collaboration between two different organizations:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…This gender-related difference could be associated to the dominant role of fathers in shaping their children’s sport experiences and the male relevant role in the sports domain [ 64 , 65 ]. In considering that parents with a sport-specific cultural capital could help their children to persist and succeed in their chosen sport [ 66 ], positive results could be expected from the involvement in the sporting community of women not directly involved in sport but supporting their talented and elite progeny [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This gender-related difference could be associated to the dominant role of fathers in shaping their children’s sport experiences and the male relevant role in the sports domain [ 64 , 65 ]. In considering that parents with a sport-specific cultural capital could help their children to persist and succeed in their chosen sport [ 66 ], positive results could be expected from the involvement in the sporting community of women not directly involved in sport but supporting their talented and elite progeny [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Danish elite sport system is broadly managed by two sets of umbrella organizations that mediate development in the 98 geographical municipalities and local sport clubs. Team Denmark is a government-funded and regulated organization in charge of improving Denmark's sporting performance in a socially responsible manner (i.e., taking care of the sport and non-sport development of athletes; Skrubbeltrang et al, 2020). The Danish National Olympic Committee (DNOC) leads all national sport federations (hereafter federations).…”
Section: The Danish Sport System Context and Aim Of The Studymentioning
confidence: 99%
“…The neoliberal discourses emphasise individual responsibility and ignore cultural barriers, such as those produced by gender hierarchies (Brunila et al 2011;Brunila and Ylöstalo 2015). In similar vein, DC policies and practices ignore the gender inequalities that exist in the male-dominated sport fields (Baird 2010;Halbert 1997;Kavoura, Ryba, and Chroni 2015;Kavoura et al 2018;Ryba et al 2015;Skrubbeltrang 2018;Skrubbeltrang et al 2018) and instead emphasise importance for the individual of working hard and making the 'right choices' (Pless 2014, 236). Being subjectified to the forces of these discourses, and to the belief that gender equality is now guaranteed in Finland (Brunila and Ylöstalo 2015), the female Finnish judo athletes downplayed the role of gender in their judo careers.…”
Section: Gendered Selvesmentioning
confidence: 99%
“…The literature further highlights that to be successful in both and to achieve a 'balanced' DC path (Stambulova et al 2015), athletes must develop the 'right' skills (Jonker et al 2010) and employ the 'right' strategies (Aquilina 2013;Brown et al 2015). Other scholars have alerted us to the effects of neoliberal understandings that hold the individual solely responsible for navigating the demands of education and career (Brunila et al 2011;Holmegaard, Ulriksen, and Madsen 2014;Leccardi 2014;Pless 2014) and instead emphasise the role of the cultural and discursive contexts in athletes' ability or inability to plan for the future (Cosh, Crabb, and Tully 2015;Ronkainen and Ryba 2018;Ryba and Wright 2010;Skrubbeltrang 2018;Skrubbeltrang et al 2018). It has been suggested that young peoples' aspirations are influenced by narratives of gender (Ekengren et al 2019;Skrubbeltrang 2018) and age (Henriksen and Mortensen 2014) as well as by the dominant belief systems, values, practices, and policy discourses that circulate in their national contexts (Leccardi 2014;Pless 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation